Design and Analysis of Native Photorespiration Gene Motifs of Promoter Untranslated Region Combinations Under Short Term Abiotic Stress Conditions - Basu, Debarati; South, Paul F. (Frontiers in Plant Science, 2022)
Quantitative traits are rarely controlled by a single gene, thereby making multi-gene transformation an indispensable component of modern synthetic biology approaches. However, the shortage of unique gene regulatory elements (GREs) for the robust simultaneous expression of multiple nuclear transgenes is a major bottleneck that impedes the engineering of complex pathways in plants. In this study, we compared the transcriptional efficacies of a comprehensive list of well-documented promoter and UTR sequences side by side. The strength of GREs was examined by a dual luciferase assay in conjunction with transient expression in tobacco. In addition, we created suites of new GREs with higher transcriptional efficacies by combining the best performing promoter-UTR sequences. We also tested the impact of elevated temperature and high irradiance on the effectiveness of these GREs. While constitutive promoters ensure robust expression of transgenes, they lack spatiotemporal regulations exhibited by native promoters. Here, we present a proof-of-principle study on the characterization of synthetic promoters based on cis-regulatory elements of three key photorespiratory genes. This conserved biochemical process normally increases under elevated temperature, low CO2, and high irradiance stress conditions and results in ~25% loss in fixed CO2. To select stress-responsive cis-regulatory elements involved in photorespiration, we analyzed promoters of two chloroplast transporters (AtPLGG1, and AtBASS6) and a key plastidial enzyme, AtPGLP using PlantPAN3.0 and AthaMap. Our results suggest that these motifs play a critical role for PLGG1, BASS6 and PGLP in mediating response to elevated temperature and high-intensity light stress. Besides the availability of genetic elements that control the abundance of recombinant proteins, correct subcellular localization is another critical aspect in synthetic biology. Here we have reported four different chloroplast targeting peptides that can efficiently localize foreign protein into the stroma. These findings will not only enable the advancement of metabolic and genetic engineering of photorespiration but will also be instrumental in related synthetic biology approaches.